Water isotope values and chemical parameters in time series samples (March 2020 - January 2021) from Müggelsee, Germany - Bernhard Aichner; David Dubbert; Sarah-Faye Harpenslager; Gregorio Alejandro López Moreira Mazacotte (PANGAEA, 2021)
Water isotopes (δ2H and δ18O) were analyzed in samples collected in lakes associated to major riverine systems in northeastern Germany throughout 2020. This sub-dataset is derived from water samples taken before the outflow of Müggelsee. Sampling was conducted biweekly from March 2020 to January 2021. Samples were taken with a pipette from 40-60 cm below water surface and directly transferred into a measurement vial. Isotope analysis was conducted at IGB Berlin, using a Picarro L2130-i cavity ring-down spectrometer. Water chemical and physical parameters are daily average values derived from the Müggelsee long-term data monitoring station (https://emon.igb-berlin.de/grosser_mueggelsee.html). The data give information about the seasonal isotope amplitude at Müggelsee over the studied time period.
In: Aichner, Bernhard; Dubbert, David; Kiel, Christine; Kohnert, Katrin; Ogashawara, Igor; Jechow, Andreas; Harpenslager, Sarah-Faye; Hölker, Franz; Singer, Gabriel; Grossart, Hans-Peter; Nejstgaard, Jens Christian; Wollrab, Sabine; Berger, Stella A; Goldhammer, Tobias; Schmid, Franziska; López Moreira Mazacotte, Gregorio Alejandro; Levertz, Constancia; Heidbüchel, Patrick; Müller, Uta; Hilt, Sabine (2021): Water isotope values from northeastern German lake systems 2020 et seq [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.935633